China in the transition to a low-carbon economy - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
China, from its own perspective cannot afford to, and from an international perspective, is not allowed to continue on the conventional path of encouraging economic growth at the expense of the environment. The country needs to transform its economy to effectively address concern about a range of environmental problems from burning fossil fuels and steeply rising oil import and international pressure to exhibit greater ambition in fighting global climate change. This paper first discusses China's own efforts towards energy saving and pollutants cutting, the widespread use of renewable energy and participation in clean development mechanism, and puts carbon reductions of China's unilateral actions into perspective. Given that transition to a low carbon economy cannot take place overnight, the paper then discusses China's policies on promoting the use of low-carbon energy technologies and nuclear power and efforts to secure stable oil and gas supplies during this transition period. Based on these discussions, the paper provides some recommendations on issues related to energy conservation and pollution control, wind power, nuclear power, clean coal technologies, and overseas oil and gas supplies, and articulates a roadmap for China regarding its climate commitments to 2050.
Keywords: Q42; Q48; Q52; Q54; Q58; 330; Energy Saving; Renewable Energy; Clean Development Mechanism; Nuclear Power; Power Generation; Oil and Gas; Post-Copenhagen Climate Negotiations; China